In silico studies on recreational drugs: 3D quantitative structure activity relationship prediction of classified and de novo designer benzodiazepines. (5th September 2022) - Catalani, Valeria; Floresta, Giuseppe; Botha, Michelle; Corkery, John Martin; Guirguis, Amira; Vento, Alessandro; Abbate, Vincenzo; Schifano, Fabrizio
Abstract: Currently, increasing availability and popularity of designer benzodiazepines (DBZDs) constitutes a primary threat to public health. To assess this threat, the biological activity/potency of DBZDs was investigated using in silico studies. Specific Quantitative Structure Activity Relationship (QSAR) models were developed in Forge™ for the prediction of biological activity (IC50 ) on the γ‐aminobutyric acid A receptor (GABA‐AR) of previously identified classified and unclassified DBDZs. A set of new potential ligands resulting from scaffold hopping studies conducted with MOE ® was also evaluated. Two generated QSAR models (i.e. 3D‐field QSAR and RVM) returned very good performance statistics ( r 2 = 0.98 [both] and q 2 = 0.75 and 0.72, respectively). The DBZDs predicted to be the most active were flubrotizolam, clonazolam, pynazolam and flucotizolam, consistently with what reported in literature and/or drug discussion fora. The scaffold hopping studies strongly suggest that replacement of the pendant phenyl moiety with a five‐membered ring could increase biological activity and highlight the existence of a still unexplored chemical space for DBZDs. QSAR could be of use as a preliminary risk assessment model for (newly) identified DBZDs, as well as scaffold hopping for the creation of computational libraries that could be used by regulatory bodies as support tools for scheduling procedures. Abstract : Drug design exercises highlight the existence of a still unexplored chemical space for designer benzodiazepines (DBZDs) and suggest that replacement of the pendant phenyl moiety with a five‐membered ring could increase their biological activity. 3D QSAR models were developed as predictive and preliminary risk assessment tools for (newly) identified DBZDs.